Autophagy in major human diseases - Klionsky, Daniel J; Petroni, Giulia; Amaravadi, Ravi K; Baehrecke, Eric H; Ballabio, Andrea; Boya, Patricia; Bravo‐San Pedro, José Manuel; Cadwell, Ken; Cecconi, Francesco; Choi, Augustine M K; Choi, Mary E; Chu, Charleen T; et al. (The EMBO journal, 2021)
Autophagy is a core molecular pathway for the preservation of cellular and organismal homeostasis. Pharmacological and genetic interventions impairing autophagy responses promote or aggravate disease in a plethora of experimental models. Consistently, mutations in autophagy‐related processes cause severe human pathologies. Here, we review and discuss preclinical data linking autophagy dysfunction to the pathogenesis of major human disorders including cancer as well as cardiovascular, neurodegenerative, metabolic, pulmonary, renal, infectious, musculoskeletal, and ocular disorders. Graphical Abstract This review provides an exhaustive overview of the contribution of autophagy to multiple pathological phenotypes in vivo , and discusses the therapeutic potential of autophagy modulation in disease prevention and treatment.